Friedrich Ebert Germany - Harmer, H. J. P. (Haus histories, 2008)
On 9 November 1918 Ebert became Imperial Chancellor as revolution broke out in Berlin. He opposed the radical left, declaring, 'Without democracy there is no freedom. Violence, no matter who is using it, is always reactionary', but he compromised Weimar democracy by his dependence on the army command and his use of the para-military Freikorps against the left. Ebert headed a joint SPD-USPD government until elections were held to a National Constituent Assembly in January 1919. Ebert became president of the new Weimar Republic (Germany's first democratically elected head of state) and retained office in a turbulent period in German politics. There were arguments among the Allies over how Germany should be treated, as France, Britain and the United States prioritised different objectives. In May 1919, the terms of the Treaty - on reparations, war guilt clause, loss of territories in Europe and colonies, limitations on armed forces - were presented to German representatives, precipitating opposition in government and the Armed Forces, and heated discussion in Cabinet. He continued as President until 1925, forced to confront the issues that arose from the Treaty and its political and economic consequences. After his death came the unravelling of the Treaty and the book examines how much of a part it played in creating the circumstances of the Second World War.